Analysis of a preferential action of alfa-amylase from B. licheniformis towards amorphous regions of waxy maize starch - Foresti, María Laura (2014)
Waxy maize starch was subjected to -amylase (Bacillus licheniformis) hydrolysis in buffered medium todetermine the evolution of reaction in quantitative terms and also in terms of the morphology and crys-tallinity of the partially hydrolyzed starch granules. Gathered data allowed studying the pattern of actionof this alfa-amylase over waxy maize starch granules, with particular focus on a preferential hydrolysis ofthe amorphous regions of starch. Results showed that waxy maize starch hydrolysis followed a two-stagekinetic profile with an initial stage characterized by high reaction rate, followed by a slower second stage.The change of hydrolysis rate occurred at approximately 6 h of reaction, a time for which X-ray diffrac-tion data quantitatively analyzed by three different techniques showed a maximum of crystallinity inpartially hydrolyzed granules. Scanning electron microscopy images illustrated the action of -amylaseswhich implied the exoerosion of the granules surface, the entry of -amylases into the granules throughradial channels, their endoerosion towards the granule exterior, and their fragmentation. Fragmentationof waxy maize starch granules revealed internal layered structures of starch which were interpreted ashydrolyzed/non-hydrolyzed growth rings. Under the conditions chosen, kinetic, electron microscopy andX-ray data all gave evidence of a preferential action of -amylase from Bacillus licheniformis towards theless ordered regions of waxy maize starch. Results showed that, provided the proper hydrolysis time ischosen, starch granules with increased crystallinity can be obtained by a pure enzymatic treatment.